Not Only Systemin: Prosystemin Harbors Other Active Regions Able to Protect Tomato Plants - Molisso, Donata; Coppola, Mariangela; Buonanno, Martina; Di Lelio, Ilaria; Aprile, Anna Maria; Langella, Emma; Rigano, Maria Manuela; Francesca, Silvana; Chiaiese, Pasquale; Palmieri, Gianna; Tatè, Rosarita; Sinno, Martina; et al. (Frontiers in Plant Science, 2022)
Prosystemin is a 200-amino acid precursor expressed in Solanaceae plants which releases at the C-terminal part a peptidic hormone called Systemin in response to wounding and herbivore attack. We recently showed that Prosystemin is not only a mere scaffold of Systemin but, even when deprived of Systemin, is biologically active. These results, combined with recent discoveries that Prosystemin is an intrinsically disordered protein containing disordered regions within its sequence, prompted us to investigate the N terminal portions of the precursor, which contribute to the greatest disorder within the sequence. To this aim, PS1-70 and PS1-120 were designed, produced, and structurally and functionally characterized. Both the fragments, which maintained their intrinsic disorder, were able to induce defense-related genes and to protect tomato plants against Botrytis cinerea and Spodoptera littoralis larvae. Intriguingly, the biological activity of each of the two N-terminal fragments and of Systemin is similar but not quite the same and does not show any toxicity on experimental non-targets considered. These regions account for different anti-stress activities conferred to tomato plants by their overexpression. The two N-terminal fragments identified in this study may represent new promising tools for sustainable crop protection.